O tempo na neurose obsessiva: um estudo psicanalítico - Capote, Natercio Antonio Ferreira (2019)
The present research investigates the ways of time attendance in the defense mechanisms of obsessional neurosis. From the Freudian formulation of atemporality as a characteristic of the mode of operation of the primary process, the research has taken as its axis of problematization the fact that the understanding we can give to this characteristic of the unconscious requires thinking about the passage from this mode of functioning of the psychic apparatus to another mode of functioning proper to the logic of consciousness, in other words, it requires thinking about the relations between the two modes of functioning of the psychic apparatus. This relationship appears in metapsychological formulations that assume capital importance when Freud approaches obsessional neurosis, such as formulations around the insistence of the traumatic past, the “afterwardness” and the expectant anguish. In order to deepen the investigation of such formulations, we carried out bibliographical research that had as fundamental source the work of Freud in the period from 1893 to 1937. The chosen texts express the course of the Freudian formulations in the (said) pre-psychoanalytic period and in the period of metapsychological construction of the first and second topical. First, we present Freud's initial formulations on trauma and defense, noting how the discussion about the etiology of neuroses places particular emphasis on the insistence of a traumatic sexual past to delineate a distinction between hysteria and obsessional neurosis. Then we return to the case of the Rat Man, seeking to apprehend the Freudian propositions about the proper way of structuring the obsessional neurosis and to understand how the time appears in such propositions. Finally, we seek to draw conclusions from this path by conducting a more specific analysis of time and if its mode of incidence in the propositions that affirm that there is an early sexual experience in this neurosis articulated to anticipation in the constitution of the I. By the last chapter, we emphasize the main forms of time attendance in the obsessive defense, namely: the character of insistence and incompleteness of the past; the temporal contraction and the linking of the past to the afterwardness; the simultaneity; the rhythmic oscillation of inhibition; the impression of the loss of time; retroactive annulment; the delay in the thoughts; the perpetual and inconclusive defense of the I; the anticipation, the procrastination and the waiting; the still or stationary time attached to an impression of imprisonment.